Design and synthesis of reactive polymers containing perfluorocyclobutyl (PFCB) and hydroxyl moieties for post-functionalization of PFCB aryl ether polymers. (14th June 2016) - Hong, Jiangjian; Bi, Liping; Li, Shining; Jia, Guangyao; Zhu, Yuanqin; Li, Guanghua; Huang, Zuqiang
Abstract: A novel class of perfluorocyclobutyl (PFCB)-containing reactive polymer with adjustable phenolic hydroxyl contents (PFCB-OH-xx) has been developed. A serial of PFCB-OH-xx polymers with high molecular weights ( M w > 100, 000) and narrow molecular weight distributions ( M w / M n < 1.15), were facilely prepared from 2-methoxy-1, 4-bis(trifluorovinyloxy)phenyl via thermal cyclopolymerization and demethylation reactions. The monomer and polymers were characterized by FT-IR and NMR spectra. PFCB-OH-xx polymers exhibit good thermal stability and excellent solubility in common organic solvents. Initial investigation of the use of PFCB-OH-xx polymers as precursors in post-functionalization of PFCB aryl ether polymers, was successfully accomplished by a nucleophilic ring-opening reaction between the phenolic hydroxyl groups and 1, 3-propanesultone. The degree of functionalization can be readily controlled by adjusting the hydroxyl contents of PFCB-OH-xx polymers. This work demonstrates that the designed PFCB-OX-xx polymers could be a class of promising precursor for development of new functional PFCB aryl ether polymers. Graphical abstract: Highlights: A new aryl trifluorovinyl ether monomer (MOTFVB) with a methoxy group was designed and synthesized. Perfluorocyclobutyl (PFCB)-containing reactive polymers (PFCB-OH-xx) with adjustable phenolic hydroxyl contents have been developed from MOTFVB. Post-functionalization of PFCB aryl ether polymers with sulfopropyl groups was accomplished using PFCB-OH-xx as precursors. PFCB-OX-xx could be a class of promising precursor for development of new functional PFCB aryl ether polymers.